Green supply chain management: Exploring research, challenges, and opportunities through bibliometrics - Fahlevi Mochammad; Dandi Mochamad; Dahlan Sahara Putri; Dahlan Olivia Putri; Asetya Dimvy Rusefani (E3S Web of Conferences)
Increasing global pollution and resources scarcity problems in marketplaces have resulted in Green Supply Chain Management (GSCM) being placed as one of the most important themes of corporate strategies. This study explores GSCM and its relationship with sustainable supply chain management (SSCM) in the context of further directing a stream of future research on such dynamic and vital topic. We employ a bibliometric analysis to trace the dynamics of knowledge production in GSCM, specifically looking at its most salient research themes, trends and thought leaders within the field. The information used was obtained from the Scopus database, with a total of 234 documents coming out in years comprising 2020–2024. The analysis finds interesting themes like green practices integration, supply chain resilience and technology role in GSCM’s global application. The results underscore a critical need for further study and implementation of GSCM initiatives to both tackle key planetary challenges and safeguard supply chain resilience and sustainability.